Barriers and facilitators to screen for and address social needs in primary care practices in Maryland: a qualitative study - Kazi, Sadaf; Starling, Claire; Milicia, Arianna; Buckley, Bryan; Grisham, Rachel; Gruber, Emily; Miller, Kristen; Arem, Hannah (Frontiers in Health Services, 2024)
BackgroundSocial needs screening can help modify care delivery to meet patient needs and address non-medical barriers to optimal health. However, there is a need to understand how factors that exist at multiple levels of the healthcare ecosystem influence the collection of these data in primary care settings.MethodsWe conducted 20 semi-structured interviews involving healthcare providers and primary care clinic staff who represented 16 primary care practices. Interviews focused on barriers and facilitators to awareness of and assistance for patients' social needs in primary care settings in Maryland. The interviews were coded to abstract themes highlighting barriers and facilitators to conducting social needs screening. The themes were organized through an inductive approach using the socio-ecological model delineating individual-, clinic-, and system-level barriers and facilitators to identifying and addressing patients' social needs.ResultsWe identified several individual barriers to awareness, including patient stigma about verbalizing social needs, provider frustration at eliciting needs they were unable to address, and provider unfamiliarity with community-based resources to address social needs. Clinic-level barriers to awareness included limited appointment times and connecting patients to appropriate community-based organizations. System-level barriers to awareness included navigating documentation challenges on the electronic health record.ConclusionsOvercoming barriers to effective screening for social needs in primary care requires not only practice- and provider-level process change but also an alignment of community resources and advocacy of policies to redistribute community assets to address social needs.